The use of pattern recognition for classification of Indonesian ginger (Zingiber officinale var. amarum) based on antioxidant activities and FTIR spectra - Anita Agustina Styawan, Ratna Asmah Susidarti, Purwanto Purwanto, Irnawati Irnawati, Abdul Rohman (Journal of Applied Pharmaceutical Science, 2023)
One of the herbals widely employed in Indonesian Traditional medicine for preventing diseases and promoting human health is ginger (Zingiber officinale Roscoe). The active components in ginger contributed to their biological activities; however, the levels of active components depend on some factors such as altitudes and harvesting time. This study intended to use the chemometrics technique for the classification and discrimination of Indonesian ginger using antioxidant activities, total determination of phenolics compounds (TPC), total determination of flavonoid compounds (TFC), and Fourier Transform Infra Red (FTIR) spectra as variables. The samples of ginger variety emprit (Z. officinale Roscoe) were obtained from 14 locations: Bantul, Kulon Progo (Yogyakarta), Banyumas, Boyolali, Karanganyar, Magelang, Purworejo, Semarang, Temanggung, Wonogiri, Wonosobo (Central Java), Magetan, Pacitan, and Ponorogo (East Java). Principal component analysis (PCA) results revealed that Indonesian ginger could be discriminated and classified using scores of 1st components (PC1) and 2nd components (PC2) applying antioxidant activity, TPC, and TFC as variables. Based on the loading plot of PCA, there is a high correlation between antioxidant activity and TFC (R2 = 0.9339) and a moderate correlation between antioxidant activity and TPC (R2 = 0.7395). Hierarchical cluster analysis informed that Indonesian ginger could be clustered, in which gingers from Semarang and Wonosobo revealed the highest similarity and were first joined. Using FTIR spectra as variables, PCA is also capable of discriminating Indonesian ginger according to its origin. There is an agreement in PCA results using both FTIR spectra and antioxidant activity, TPC, and TFC in which gingers from Semarang and Wonosobo revealed similar PC1 and PC2. We concluded that the application of the pattern recognition technique is an effective tool for the discrimination and characterization of ginger in specific and herbal components in general.